Remark on Exponential Decay of Ground States for N-Laplacian Equations (Journal of Partial Differential Equations, 2009)
We study exponential decay property of radial ground states to a class of N-Laplacian elliptic equations in the whole space R^N. Their decay rates as |x|→∞ are obtained explicitly.
Keywords: N-Laplacian; ground states; exponential decay